2011
DOI: 10.1007/s11357-011-9259-8
|View full text |Cite
|
Sign up to set email alerts
|

Aging might increase myocardial ischemia / reperfusion-induced apoptosis in humans and rats

Abstract: Previous studies indicated aging results in the significant cardiac function decreasing and myocardial apoptosis increasing in normal humans or rats. Additionally, animal experiments demonstrated aging increased myocardial ischemia / reperfusion (MI/R)-induced apoptosis. However, whether more myocardial apoptosis happen in the old acute myocardial infarction (AMI) patients is unclear. Reperfusion injury-induced apoptosis is an important cause of heart failure. This study determined the effect of aging upon myo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(60 citation statements)
references
References 28 publications
(24 reference statements)
3
55
0
1
Order By: Relevance
“…Aging has been found to reduce the angiogenic response to ischemic injury in animal models 24 and result in greater ischemia reperfusion injury and apoptosis. 25,26 A loss of cardioprotection and a decreased response to ischemic precondition have also been noted with aging, 27,28 although this has not been consistent across all studies. 29 In addition, relative to older adult donors, younger adult donors have been associated with some studies with a decreased incidence of cardiac allograft vasculopathy and improved long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…Aging has been found to reduce the angiogenic response to ischemic injury in animal models 24 and result in greater ischemia reperfusion injury and apoptosis. 25,26 A loss of cardioprotection and a decreased response to ischemic precondition have also been noted with aging, 27,28 although this has not been consistent across all studies. 29 In addition, relative to older adult donors, younger adult donors have been associated with some studies with a decreased incidence of cardiac allograft vasculopathy and improved long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that older guinea pig, rat, and mouse hearts are less sensitive to cardioprotective strategies such as ischemic or anesthetic preconditioning compared with younger hearts (5,7,31,33,34). Other reports indicate that aging exacerbates apoptosis (25) and cardiac damage after ischemia (18); however, not all studies have observed increased infarct size in aged rats (32,34).…”
mentioning
confidence: 99%
“…13,26 In mice, regression occurs even after only two weeks of detraining train which indicates that cardiac mass in mice returned to basal state after about 21 days of detraining. 27 According to Liu et al 28 age may contribute to the loss of more than 30% of cardiac myocytes without heart disease, and can lead to myocardial dysfunction or heart failure. 29 In addition, These authors also reported that the expression of protein Bcl-2 and Bax increased in the heart of old Fischer-344 rats under physiological conditions.…”
Section: 18mentioning
confidence: 99%